(untitled) (Journal of Educational Sciences, 2024)
The article examines the phenomenon of outsourcing as a practice in which doctoral students hire other people to perform their academic tasks, for example, writing a doctoral dissertation. Academic integrity is an important part of the educational process, and its violation negatively affects the future career of a doctoral student and the reputation of the institution as a whole, therefore, the study was aimed at identifying and analyzing the reasons why doctoral students decide to outsource the writing of their academic papers, especially dissertations, as well as assessing contextual factors influencing this decision. To achieve this goal, a constructivist paradigm was used, which determined a qualitative study, including interviews with doctoral students, which allowed to gain a deep understanding of their motivation and factors influencing the choice of outsourcing. The study revealed that the key factors motivating doctoral students to outsourcing are a low level of academic abilities, research competence, lack of knowledge of methodology, time constraints, fear of failure, the desire to defend themselves in time, and sometimes it’s just laziness and unwillingness to study. It has also been found that academic misconduct may involve collusion with colleagues, friends, and family members, so further research may focus on the role of the family in facilitating academic misconduct and on the ethical and legal aspects of outsourcing academic work. Understanding the motivation of doctoral students and the contextual conditions that contribute to academic misconduct is important for developing learning and control strategies in the postgraduate education system in order to maintain academic integrity and integrity. Keywords: academic fraud, outsourcing, essay factory, ChatGPT, subjects of postgraduate education.